Plants: Evolution and diversity - Ingrouille, Martin (Cambridge University, 2012)
Plants are so much part of our environment that we often take them for granted. How did this array of form and habitat come about, and how do we humans interact with the plant kingdom? This book provides a consideration of these questions and throws light in a new way on the complexity, ecology, evolution and development of plants and our relationship with them. Illustrated throughout with numerous line diagrams and colour photographs, the book provides a unique source of information about the fascinating lives that plants lead and the way in which our lives are inextricably linked to theirs. It will be particularly useful to students seeking a more ecological and process-oriented approach than is available in other plant science textbooks.